Pengukuran Efektivitas Infografis Pada Portal Berita Online Kompas.com - Zahrina Rahmani Humairoh; Dian Prajarini (AKSA: Jurnal Desain Komunikasi Visual, 2019)
Online media in greater demand information because the community in looking for quick and easy to access, one of the pioneer is Kompas.com which become a reference to journalism amid all the uncredible information. Nowadays, the Public has limited time to read and understand the news that contains much texting, that is why kompas.com presenting news in infographics with that look attractive but can convey that complex information being easy and fast to understand by the Society. This study focused on the right standard infographics and submission of a simple understanding of infographics that rises for five months of every month taken samples three randomly infographics. The purpose of this research is to evaluate infographic design in the online news website Kompas.com and to see whether the purpose in Kompas.com infographics suitable for the purpose with four important uses categories: usability, readable, design, and aesthetics. The methodology used quantitative methods. The data to the questionnaire online to FLP communities with four variables that usability, readability, design, and aesthetics. The validity test is using moment Pearson; and readability test using Alfa Cronbach. Data analysis using descriptive statistics. Based on data analysis and discussion in this research can be concluded that infographic Kompas.com filled four variables assessment that usability is 80,2 %, Readable is 80,3 %, the design is 82,6 %, and aesthetics is 79,4 %. This shows that the making of Kompas.com infographics is in accordance with generation purposes infographic, which is understandable, easy to read, good in visual, and straight information.